2012
DOI: 10.1097/ajp.0b013e31823ae69e
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Pain Modulation and Autonomic Responses in Fibromyalgia and Irritable Bowel Syndrome Patients

Abstract: Our results confirm the presence of graded levels of somatic hyperalgesia across patients with IBS and FM. A similar pattern of result was observed for pain inhibitory dysfunctions. These pain processing changes were accompanied by abnormal autonomic responses, which maintained patients (principally patients with FM) in a state of sympathetic hyperactivity. Results suggest that patients with IBS and FM may present common, but graded, pain processing and autonomic dysfunctions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 63 publications
4
66
1
3
Order By: Relevance
“…44 Chalaye et al 11 has recently shown that patients with FM show less increase in blood pressure during CPT, associated with less efficient CPM, raising the possibility that the CPM effect might be, at least in part, mediated by change in the autonomic balance. These authors have shown that for patients with FM, the dominant autonomic tone is sympathetic, as opposed to parasympathetic dominance in controls Chalaye et al 10 For IBS, Coffin et al 13 have shown that using a rectal balloon as conditioning stimulus did not reduce the RIII response in patients compared with controls. King et al 37 April 2015 · Volume 156 · Number 4 · Supplement 1 www.painjournalonline.com S27 IBS compared with controls, but to a smaller extent than TMDs.…”
Section: Idiopathic Pain Syndromesmentioning
confidence: 99%
“…44 Chalaye et al 11 has recently shown that patients with FM show less increase in blood pressure during CPT, associated with less efficient CPM, raising the possibility that the CPM effect might be, at least in part, mediated by change in the autonomic balance. These authors have shown that for patients with FM, the dominant autonomic tone is sympathetic, as opposed to parasympathetic dominance in controls Chalaye et al 10 For IBS, Coffin et al 13 have shown that using a rectal balloon as conditioning stimulus did not reduce the RIII response in patients compared with controls. King et al 37 April 2015 · Volume 156 · Number 4 · Supplement 1 www.painjournalonline.com S27 IBS compared with controls, but to a smaller extent than TMDs.…”
Section: Idiopathic Pain Syndromesmentioning
confidence: 99%
“…There are only two ways in which syndromes can be linked: either the first initiates a process that leads to the second or a preceding process leads to both. Candidates for such a process have emerged from studies of individual FSSs and include generalized amplification of pain and sensory processing [25][26][27], autonomic dysfunction [28], and abnormalities in the hypothalamus-pituitary-adrenal axis [29]. Investigators for some years have speculated that a shared pathogenesis underlies this polysyndromic phenotype [5,20,[30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Los estudios metanalíticos sobre la VFC en la FM concluyen que en la mayoría de las investigaciones desarrolladas encuentran una menor VFC en los sujetos con FM en comparación con los sanos (Meeus et al, 2013;del Paso et al, 2011;Tracy et al, 2016) y esta diferencia la interpretan como indicadora de una regulación autónoma global disminuida propia de la FM (Chalaye et al, 2012;da Cunha et al, 2011;Kulshreshtha y Deepak, 2013;Lerma et al, 2011). La alteración de la VFC en la FM, en comparación con los controles sanos, también se caracteriza por presencia a lo largo del sueño de hiperactividad simpática, hipoactividad parasimpática y menor VFC (Álvaro y Traver, 2010;Díaz-Piedra et al, 2014;Lerma et al, 2011;Sañudo et al, 2010).…”
Section: Introductionunclassified